Installation of brickwall for Spice Hotel on Jalan Tun Dr Awang , Mukim 12 Daerah Barat Daya Pulau Pinang / Mohamad Irwan Mohamad Azlan Shah - Mohamad Azlan Shah, Mohamad Irwan (Universiti Teknologi Mara, Perak, 2018)
MZA Integrated Resources is a company that been registered on 5th February 2009. The main purpose of this company is to give a comprehensive and integrated services in consultation of supplying, building and technical proposal to meet the needs and wants of the customer that includes government and non-government. This company is established and managed by a dynamic organisation, a bumiputra professional entities that skilful, knowledgeable in the field provided and various resources in result of perfect work completion.